Microbial carbon use efficiency predicted from genome-scale metabolic models - Mustafa Saifuddin (Nature Portfolio, 2019)
Microbial respiration releases carbon from the soil. Here, the authors estimate bacterial carbon use efficiency in soils for over 200 species using constraint-based modeling, incorporate the values into an ecosystem model, and find that shifts in community composition may impact carbon storage.